Crash Reconstruction of Mixed-Vehicle Collision Using PC-Crash - Paudel, Hem; Pradhananga, Rojee (International Journal on Engineering Technology and Infrastructure Development, 2026)
Road traffic crashes are a leading cause of injury and property damage worldwide, which has disclosed the need of taking systematic and precise reconstruction techniques. This paper presents the simulation of real-world road crash between a minitruck and a motorcycle using PC-Crash Software. The reconstruction followed a structured four stage workflow, i.e. the reconstruction of the accident scene, Vehicle modeling, crash simulation, and iterative validation. Calibrated simulations established pre-impact speeds of 34 km/h for the minitruck and 18 km/h for the motorcycle, with post-impact rest positions and vehicle orientations showing strong correspondence with physical scene evidence. Most significant dynamic parameters such as head acceleration, contact force and energies were obtained to describe the severity of collisions. The motorcycle was modeled as a complete multibody system including the biomechanical aspects of the rider, which allowed to simulate the realistic behavior of a human body during the impact event. The results show that PC- Crash can be very appropriate in reconstruction of mixed-vehicle collisions within the context of low- and middle-income countries like Nepal, where crash databases are not centralized, and field evidence is represented by police documentation.